2012
DOI: 10.1136/heartjnl-2012-302126
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin plus corticosteroid to prevent coronary artery abnormalities in Kawasaki disease: a meta-analysis

Abstract: Combination of corticosteroid with the conventional regimen of IVIG as an initial treatment strategy could reduce the risk of coronary abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 42 publications
0
84
0
1
Order By: Relevance
“…A recent metaanalysis that included these trials, using different regimens of steroids and different prediction scores, found that a combination of corticosteroid with standard-dose IVIG as an initial treatment in high-risk patients reduced the rate of coronary artery abnormalities. 191 Thus, the addition of corticosteroid therapy to IVIG and ASA in the primary therapy of KD lowers the prevalence of coronary artery abnormalities, duration of fever, and inflammation among Japanese children at highest risk for IVIG resistance. However, the Japanese scoring systems for IVIG resistance and aneurysms have low sensitivity in North American populations.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…A recent metaanalysis that included these trials, using different regimens of steroids and different prediction scores, found that a combination of corticosteroid with standard-dose IVIG as an initial treatment in high-risk patients reduced the rate of coronary artery abnormalities. 191 Thus, the addition of corticosteroid therapy to IVIG and ASA in the primary therapy of KD lowers the prevalence of coronary artery abnormalities, duration of fever, and inflammation among Japanese children at highest risk for IVIG resistance. However, the Japanese scoring systems for IVIG resistance and aneurysms have low sensitivity in North American populations.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…[14][15][16][17][18][19] A meta-analysis of these studies concluded that the addition of corticosteroids to intravenous immunoglobulin resulted in fewer coronary artery abnormalities than with treatment with intravenous immunoglobulin alone (OR 0·3, 95% CI 0·18-0·5). 20 However, heterogeneity in patient selection and treatment protocols severely limits application to our patient population. Three studies assessed 3-5 days of intravenous methylprednisolone (2 mg/kg per day) followed by a 2-4 week oral taper, 14,16,19 whereas the remaining three studies used a single pulse of intravenous methylprednisolone (30 mg/kg per day).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of clinical trials evaluating the use of corticosteroids plus IVIG are confusing, Chen et al found that significantly fewer patients receiving IVIG plus corticosteroids developed coronary artery aneurysm than those receiving IVIG alone. 13 Our patient underwent the treatment with corticosteroid because he was resistant to 2 doses of IVIG. No coronary artery aneurysm was detected at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%